(untitled) (Journal of the College of Basic Education, 2022)
The study of the geomorphological role practiced by man is one of the very important studies because of its importance in revealing his capabilities in changing the terrestrial appearance and forming many geomorphological forms during the practice of his various activities, especially after the use of huge machines in those activities, as his role is no less important than the role of natural factors. In the formation of the various geomorphological forms, after the land was almost flat and free of barriers, he directly entered it and dug irrigation and drainage canals that completely changed the shape of the land, especially after the implementation of the Agricultural Reclamation Law in the seventies and eighties of the last century,It also built roads and excavated the earth and extracted its water and other components, such as the clay that he used in construction after its manufacturing processes, and he was proud of it in the brick production factories located in the region. The borders after the outbreak of the war with Iran, which he used in military operations at the time, and built thousands of hills and placed cannons on them, which are still standing despite the passage of more than thirty years since its establishment, as well as he built many shelters to protect soldiers and military machines from bombing, which today resemble the bad lands that are formed Natural processes, this is new, or in the past, he built castles and fortresses, which, after their collapse, became huge hills in the region.